K problému výskytu syndromu lehkých mozkových dysfunkcí u dĕtí - Gebhart, J A; Dytrych, Z; Tyl, J; Srám, R J (Ceskoslovenska psychiatrie, 1990)
The paper explains the social need of epidemiological research of the incidence of behavioural and learning disorders associated with the syndrome of minimal brain dysfunction (MBD). The authors draw attention to the continuous incidence of various inborn developmental defects in the population from very severe to mild ones and provide evidence of it on the basis of research in behavioural teratology. They discuss the possible relationship of MBD with psychosocial and chemical influences. They discuss preventive measures to avoid secondary deterioration of the mental and general health status. A specific approach to teaching of these children and psychotherapeutic influencing of parents is essential and one cannot rely only on early therapeutic effects by drugs. To implement preventive measures the latter must be planned on the background of knowledge regarding the incidence in the child population and the severity of the affection. This calls for the elaboration of a screening method for the early diagnosis of MBD. Knowledge of the incidence of MBD in the population along with possible aetiopathogenetic factors, will make more profound research of these association and primary prevention possible.
Keywords: Child; hyperkinetická porucha; Education, Special; Československo; speciální vzdělávání; Attention Deficit Disorder with Hyperactivity; Humans; lidé; dítě; incidence; Incidence; Czechoslovakia